Integrasi Teknologi dalam Pendidikan (Dampak Terhadap Kompetensi Guru dan Tantangan Adaptasi di Indonesia) (Prosiding Keislaman dan Sains, 2025)
This study aims to explore the trends in education and technology, and their impact on teacher competency. Qualitative methods were used to analyze data from various articles in reputable Shinta journals and international references. The results showed that technology has a significant impact on teaching methods and teacher competency. The main challenges faced are adaptation to new technologies and the development of digital skills. This article provides in-depth insights into how technology can be effectively integrated into education. This study also highlights the importance of adequate support for teachers in developing their digital skills. Thus, it is hoped that these findings can help in the development of more effective policies and training programs for teachers.